Relation between academic achievement and pupil mobility - Ratcliff, Judith (Anderson) 1936- ([Quezon City s.n.], 1969)
The purpose of this paper is to investigate the possible relationship between academic achievement and the degree of mobility of elementary school children who are mostly dependents of military personnel. In general, the many comparisons made in this study suggest that for the particular group studied, there are no clear-cut relationships between academic achievement and mobility.
Thesis (M.Ed.)--University of the Philippines
Keywords: Academic achievement